Expression of Plasma miRNA-133a is Significantly Lower in Acute Coronary Syndrome (ACS) than in Healthy/Non-ACS Subjects - Rachmawati, Ermin; Sargowo, Djanggan; Saputra, Indra Wahyu; Riskiyah, Riskiyah; Handirosiyanto, Ikhwan; Hakim, Arief Rachman; Ismail, Mahrus; Tarsadi, Tarsadi; Maulana, Syafiq; Ahdi, Iwal Reza; Puspitasari, Alvina; Wardhani, Syanindita Puspa (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: The current biomarker diagnostic modality for acute coronary syndrome (ACS), cardiac troponin, has several limitations. Emerging studies showed that micro-RNA (miR)-133a was released from infarcted heart to circulation, yet the diagnostic value of miR-133a in ACS demonstrated a conflicting result. Therefore, this study was conducted to investigate the potency of plasma miR-133a as a biomarker candidate of ACS.METHODS: This was a case-controlled study, involving ACS and control subjects. The sociodemographic and clinical characteristics were assessed through medical records. A final of 39 ACS and 31 control subjects (consist of healthy and non-ACS subjects) passed the selection procedure by demonstrating a high purity of RNA. miR-133a from ACS and control subjects were detected by quantitative polymerase chain reaction (qPCR). Expression of miR-133a was evaluated for sensitivity and specificity as an ACS biomarker diagnostic using the receiver operating characteristic (ROC) curve.RESULTS: Plasma miR-133a expression was stably found in ACS subjects. The plasma miR-133a level was lower in ACS than in control subjects. miR-133a effectively distinguished ACS subjects from healthy subjects (AUC=0.911) and exhibited high diagnostic performance, with a sensitivity of 87.1% and specificity of 100% at a cut-off value of 44.035. In an extended model including both control subjects (healthy and non-ACS with comorbid conditions), miR-133a maintained diagnostic significance (AUC=0.874), showing sensitivity of 76.9% and specificity of 100% at a cut-off value of 11.69.CONCLUSION: Plasma miR-133a is significantly lower and effectively distinguishes ACS patients from both healthy individuals and non-ACS individuals with comorbid, with a cut-off value of 11.69. Therefore, plasma miR-133a is suggested to be a good candidate for diagnostic biomarkers of ACS.KEYWORDS: circulating miRNA, miRNA-133a, acute coronary syndrome, diagnostic biomarker